Trichloro-bridged diruthenium (III,III) complexes: X-ray isomorphous structures of [Ph3X=O center dot center dot center dot H center dot center dot center dot O=XPh3][Ru2Cl7(XPh3)(2)]center dot 0.5(CH2Cl2)(H2O)(X = As or P) - de Araujo, M. P.; Queiroz, S. L.; Batista, A. A.; Panepucci, E. H.; Oliva, G.; Castellano, E. E. (Kluwer Academic Publ, 2002)
The triply chloro-bridged binuclear complexes [Ph3X=O...H...O=XPh3][Ru2Cl7(XPh3)(2)].0.5(CH2Cl2) (H2O) (X = As or P) were obtained from [RuCl3(XPh3)(2)DMA].DMA (DMA = dimethylacetamide) CH2Cl2/Et2O solution. The structures were characterized by X-ray diffraction studies. The complexes are formed from two Ru atoms bridged by three chloride anions. The two ruthenium atoms are also coordinated to two non-bridging Cl atoms and an AsPh3 or PPh3 ligand respectively. As an interesting feature, the cations of these complexes are protons, trapped in a very short hydrogen bond between two triphenylarsine or triphenylphosphine oxide molecules.